3D Bioprinting of an In Vitro Model of a Biomimetic Urinary Bladder with a Contract-Release System - Suhun Chae; Jaewook Kim; Hee-Gyeong Yi; Dong-Woo Cho (Micromachines, 2022)
The development of curative therapy for bladder dysfunction is usually hampered owing to the lack of reliable ex vivo human models that can mimic the complexity of the human bladder. To overcome this issue, 3D in vitro model systems offering unique opportunities to engineer realistic human tissues/organs have been developed. However, existing in vitro models still cannot entirely reflect the key structural and physiological characteristics of the native human bladder. In this study, we propose an in vitro model of the urinary bladder that can create 3D biomimetic tissue structures and dynamic microenvironments to replicate the smooth muscle functions of an actual human urinary bladder. In other words, the proposed biomimetic model system, developed using a 3D bioprinting approach, can recreate the physiological motion of the urinary bladder by incorporating decellularized extracellular matrix from the bladder tissue and introducing cyclic mechanical stimuli. The results showed that the developed bladder tissue models exhibited high cell viability and proliferation rate and promoted myogenic differentiation potential given dynamic mechanical cues. We envision the developed in vitro bladder mimicry model can serve as a research platform for fundamental studies on human disease modeling and pharmaceutical testing.